Study on the influence of changes of air resistance athletes` taking-off speed in freestyle skiing aerials - Le, Z.; Yi, M.; Xin, W. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Freestyle skiing is a competitive sport in the open-air environment. The air resistance that athlete meets in the process of slipping, transition and entering stage determines the athletes` taking-off speed, thus affecting the performance in competition. This paper set up a function model of frontal area and time about L, T, F, DF, F and other single action in the process completed, and establishes the function between windward area and time in specific action. It studies and analyses the influence of air resistance on athlete`s taking-off speed, combining with the results of the taking-off speed calculation software. The main findings are shown as follows: When the wind speed each increases 0.8 m/s in the leaving platform phase, athlete's taking-off speed will decrease 0.4m/s. When the wind speed is low, the change of wind direction exerts little impact on athletes` taking-off speed.